Consumer protection for sale of goods under the Malaysian Sale of Goods Act 1957 and the Consumer Protection Act 1999: with special reference to quality and fitness of goods - Masum, Ahmad; Ahmad, Muhamad Hassan; Mohamed Nafees, Seeni Mohamed; Md Isa@Yusuff, Yusramizza (American Journal of Humanities and Social Sciences Research (AJHSSR), 2018)
Consumers enter into various types of contracts for supply of goods or services in their everyday lives. The consumer market is very lop-sided. Therefore, the call for consumer protection is unavoidable. Today‟s consumers need to be equipped with high consumerism knowledge and skills to be wellinformed of market developments, necessary to empower them to be better able to act, make effective decisions and to ensure that they become more empowered, savvy and resilient. However, empowered consumers will not be created without the government intervening to protect consumers with adequate legislations. This paper aims to examine the existing Malaysian laws specifically the Sale of Goods Act 1957 and the Consumer Protection Act 1999 in protecting consumers in a sale of goods transaction and determine their adequacy. The paper focuses on two important protections namely; quality and fitness of goods. The paper adopts a legal library based research methodology focusing mainly on primary and secondary legal sources. Although the aforementioned Malaysian laws continue to protect consumers of goods, the paper concludes that there is a need to completely revamp these laws in order to reflect a more uniform and modernised approach.